Pengenalan Tools Trello untuk Anggota PKK Kelurahan Meruya Utara - Nurullah Husufa; Danny Yudin Djahidin (Jurnal Pengabdian Pada Masyarakat, 2021)
INTRODUCTION OF TRELLO TOOLS FOR PKK MEMBERS IN MERUYA UTARA VILLAGE. PKK Kelurahan Meruya Utara is one of the PKK organizations located in the Kembangan area in West Jakarta. Trello Tools is a cloud-based tool that uses the Kanban method of project management. The number of program activities that must be carried out by the PKK Kelurahan Meruya Utara causes these activities not be recorded properly. Include status of each of the activities and who are the members involved in these activities. From the results of the questionnaire for participants, it can be concluded that the PPM activities support the needs of the PKK in implementing work programs.